Lithium manganese iron phosphate positive electrode material with high compaction density and preparation method of lithium manganese iron phosphate positive electrode material
By coating the surface of the lithium iron manganese phosphate cathode material with a carbon layer formed by a combination of organic and inorganic carbon sources, the problem of poor electrical conductivity and charge and discharge performance of the material is solved, and high compaction density and excellent electrochemical performance are improved.
Patent Information
- Application Number
- CN202411414443.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-21
AI Technical Summary
The conductivity and charge and discharge performance of lithium manganese iron phosphate cathode material are poor, and it is difficult to balance the powder compaction density and discharge capacity of the material, resulting in limited energy density improvement.
It is prepared by coating the surface of lithium iron manganese phosphate cathode material with a carbon layer formed by a mixture of organic carbon source and inorganic carbon source, combining a certain proportion of glucose, sucrose, carbon nanotubes and graphene as carbon sources, spray drying and sintering. , forming a high-density lithium iron manganese phosphate cathode material.
The high compaction density, low specific surface area and excellent electrochemical performance of the lithium iron manganese phosphate cathode material have been achieved, and the energy density and charge and discharge performance of the material have been improved.
Smart Images

Figure CN119340360A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode material, and in particular to a lithium manganese iron phosphate positive electrode material with a high compaction density and a preparation method thereof. Background Art
[0002] As an upgraded version of lithium iron phosphate, lithium manganese iron phosphate (LMFP) has a discharge voltage of 4.0V, which has a higher energy density than 3.4V of lithium iron phosphate. At the same capacity, the energy density of lithium manganese iron phosphate battery can be increased by about 20% compared with lithium iron phosphate battery. In addition, LMFP also has significant advantages in safety and cost-effectiveness, and is expected to become a cobalt-free cathode material for a new generation of high-energy-density power batteries, with huge market potential.
[0003] However, LMFP still has some major problems and defects: 1. Poor conductivity and charge-discharge performance: LMFP has poor conductivity, which is due to the limited lithium ion diffusion channel in its olivine structure, resulting in a low diffusion rate of lithium ions; in addition, LMFP also has low electronic conductivity, which affects the charge-discharge rate and cycle stability of the battery; when carbon coating, the carbon content is too high, although the finished product can obtain good conductivity, but the increase in carbon content will also have a negative impact on increasing the compaction density and reducing the specific surface area, which is not conducive to the effective improvement of LMFP energy density. 2. It is difficult to balance the compaction density and discharge capacity of the material powder: Generally speaking, the high compaction density will result in poor discharge capacity. For samples with excellent discharge capacity, the compaction density will be relatively low. In the process of solid-phase synthesis of LMFP, the sand milling particle size is too small. Although the finished product can obtain good electrochemical performance, its specific surface area is large, the material is easy to agglomerate, difficult to disperse, and the electrode processing is difficult, and the compaction density will also be low. In order to meet the above challenges, nano-sizing, carbon coating, element doping, solid-liquid integration and other technical means are introduced into the preparation method of LMFP, which can increase the powder compaction density of the material to 2.3g / cm 3 However, its 0.1C discharge specific capacity is below 145mAh / g. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a lithium iron manganese phosphate positive electrode material with excellent conductivity, small specific surface area and high compaction density; the second purpose of the present invention is to provide a method for preparing the above-mentioned lithium iron manganese phosphate positive electrode material.
[0005] Technical solution: The lithium iron manganese phosphate positive electrode material with high compaction density provided by the present invention has a carbon layer formed by a composite of an organic carbon source and an inorganic carbon source coated on the surface of the lithium iron manganese phosphate positive electrode material, wherein the mass ratio of the organic carbon source to the inorganic carbon source is 1.5-5:1, preferably 1.5-3:1.
[0006] Furthermore, the organic carbon source is one or more of glucose, sucrose, fructose, polyvinyl alcohol, polyethylene glycol, polystyrene, polyethylene, polypropylene, starch, cellulose, cyclodextrin, citric acid, ascorbic acid, tartaric acid, palmitic acid, oleic acid, maleic acid, malonic acid, adipic acid, stearic acid, and polyvinyl pyrrolidone.
[0007] Furthermore, the inorganic carbon source is one or more of acetylene black, carbon fiber, carbon nanotube, graphene, graphene oxide and modified materials thereof.
[0008] Furthermore, the particle size D50 of the lithium manganese iron phosphate positive electrode material is 0.12-0.45 μm.
[0009] The present invention also provides a method for preparing the above-mentioned lithium iron manganese phosphate positive electrode material, comprising the following steps:
[0010] (1) dispersing a manganese source, an iron source, a phosphorus source and a lithium source in a solvent and mixing them to obtain slurry A;
[0011] (2) dispersing a mixed carbon source including an organic carbon source and an inorganic carbon source in a solvent, mixing the mixed carbon source and adding the mixed carbon source to slurry A to obtain slurry B;
[0012] (3) Slurry B is fully ground, spray-dried, and sintered to obtain a lithium manganese iron phosphate positive electrode material with a high compaction density.
[0013] Furthermore, in step (1), the molar ratio of the manganese source, iron source, phosphoric acid and lithium source is x:1-x:1,1, wherein x is 0.5-0.8; in the slurry A, the molar concentration of the manganese source is 0.5-2.0 mol / L; and the solvent is pure water.
[0014] Furthermore, in step (2), the solid content of the slurry A is 15-45%.
[0015] Furthermore, in step (2), the mixed carbon source is 5-10% of the total mass of the manganese source, iron source, phosphoric acid and lithium source.
[0016] Furthermore, in step (2), the particle size D50 of the material obtained by grinding is 0.12-0.45 μm.
[0017] Furthermore, in step (3), the spray drying parameters are: air inlet temperature is 220-300°C, and air outlet temperature is 80-100°C.
[0018] Furthermore, in step (3), the sintering conditions are: sintering at 650-750° C. for 2-10 hours.
[0019] Invention principle: Carbon coating can improve the electronic conductivity and other properties of phosphate cathode materials. The uniform carbon layer can provide a medium for electron transfer, improve the electronic conductivity of the interface between particles and electrolytes and between particles, prevent particle growth, inhibit particle agglomeration, thereby reducing the transmission distance of lithium ions and improving ion conductivity. At the same time, it acts as a protective layer to reduce the contact between particles and electrolytes and prevent Mn 3+ It dissolves into the electrolyte and also acts as a reducing agent to prevent oxidation of the material. When using only organic carbon sources such as glucose and sucrose, they melt with the precursor material during the sintering process, causing carbon thermal reduction reaction and carbon coating of LMFP. The carbon coating layer is relatively uniform, but the coating layer will be thicker, which is not conducive to the deintercalation of lithium ions. On the other hand, more flocculent carbon will be produced, resulting in a larger specific surface area and lower compaction density. When using only inorganic carbon sources such as graphite, carbon nanotubes, and graphene, the carbon thermal reduction reaction is completed during the sintering process, and its good electronic conductivity can be inherited in the material system, but it cannot coat LMFP well, and there will be more exposed LMFP crystals, resulting in poor conduction of electrons from the inside of the LMFP crystal to the interface, and the electronic conductivity of the material is poor. The solution of using a mixture of organic carbon sources and inorganic carbon sources can take into account both carbon coating and electronic conductivity. For example, using a certain proportion of glucose, sucrose, carbon nanotubes, graphene, etc. as carbon sources, sucrose and glucose can coat a thin carbon layer on the surface of LMFP crystals to ensure the migration of electrons from the inside of LMFP crystals to the interface; while carbon nanotubes, graphene and carbon derived from organic carbon sources together construct a three-dimensional conductive network, which can well ensure the migration and conduction of electrons between LMFP crystals. Thus, high compaction, low specific surface area and excellent electrical properties of phosphate cathode materials are achieved.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the present invention can well control the carbon content in the lithium manganese iron phosphate positive electrode material by combining the organic carbon source and the inorganic carbon source at a certain mass ratio, while obtaining a higher compaction density, it also has good electrochemical properties and a lower specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The charge and discharge performance curve of the high compaction density LMFP positive electrode material prepared in Example 4 in the range of 2.0-4.5V and at a rate of 0.1C;
[0022] Figure 2 This is a scanning electron microscope image of the high compaction density LMFP positive electrode material prepared in Example 4;
[0023] Figure 3 This is the XRD of the high compaction density LMFP positive electrode material prepared in Example 4. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific embodiments and drawings.
[0025] Example 1: The high compaction density lithium iron manganese phosphate positive electrode material provided in this example is a carbon layer formed by coating the surface of the lithium iron manganese phosphate positive electrode material with a composite of an organic carbon source and an inorganic carbon source, wherein the mass ratio of the organic carbon source to the inorganic carbon source is 3:1.
[0026] The preparation method of the above positive electrode material comprises the following steps:
[0027] 1379.40g manganese carbonate, 778.97g lithium carbonate, 1207.98g iron phosphate, and 1383.46g concentrated phosphoric acid were weighed, dispersed in 9L ultrapure water and mixed evenly to form slurry A; then 3.6% glucose, 2.4% PEG and 2% carbon nanotube slurry were weighed according to the total mass, dispersed in 1.5L ultrapure water, and added to slurry A to form slurry B; then ground to D50 = 0.25 ± 0.01 microns, and sand milling was terminated; then spray dried and sintered at 720°C for 10 hours to obtain a carbon-modified high compaction density lithium manganese iron phosphate positive electrode material, namely LMFP material.
[0028] Example 2: The high compaction density lithium iron manganese phosphate positive electrode material provided in this example is a carbon layer formed by coating the surface of the lithium iron manganese phosphate positive electrode material with a composite of an organic carbon source and an inorganic carbon source, wherein the mass ratio of the organic carbon source to the inorganic carbon source is 3:1.
[0029] The preparation method of the above positive electrode material comprises the following steps:
[0030] 1379.40g manganese carbonate, 778.97g lithium carbonate, 1207.98g iron phosphate, and 1383.46g concentrated phosphoric acid were weighed, dispersed in 9L ultrapure water and mixed evenly to form slurry A; then 3.6% glucose, 2.4% PEG and 2% graphene slurry were weighed according to the total mass, dispersed in 1.5L ultrapure water, and added to slurry A to form slurry B; then ground to D50 = 0.25 ± 0.01 microns, and sand milling was terminated; then spray dried and sintered at 720°C for 10 hours to obtain a carbon-modified high compaction density lithium manganese iron phosphate positive electrode material, namely LMFP material.
[0031] Example 3: The high compaction density lithium iron manganese phosphate positive electrode material provided in this example is a carbon layer formed by coating the surface of the lithium iron manganese phosphate positive electrode material with a composite of an organic carbon source and an inorganic carbon source, wherein the mass ratio of the organic carbon source to the inorganic carbon source is 3:1.
[0032] The preparation method of the above positive electrode material comprises the following steps:
[0033] 1379.40g manganese carbonate, 778.97g lithium carbonate, 1207.98g iron phosphate, and 1383.46g concentrated phosphoric acid were weighed, dispersed in 9L ultrapure water and mixed evenly to form slurry A; then 3.6% glucose and 2.4% PEG, 1% carbon nanotube slurry and 1% graphene slurry were weighed according to the total mass, dispersed in 1.5L ultrapure water, and added to slurry A to form slurry B; then ground to D50 = 0.25 ± 0.01 microns, and sand milling was terminated; then spray dried and sintered at 720°C for 10 hours to obtain a carbon-modified high compaction density lithium manganese iron phosphate positive electrode material, i.e., LMFP material.
[0034] Example 4: The high compaction density lithium iron manganese phosphate positive electrode material provided in this example is a carbon layer formed by coating the surface of the lithium iron manganese phosphate positive electrode material with a composite of an organic carbon source and an inorganic carbon source, wherein the mass ratio of the organic carbon source to the inorganic carbon source is 1.5:1.
[0035] The preparation method of the above positive electrode material comprises the following steps:
[0036] Manganese carbonate, lithium carbonate, iron phosphate and concentrated phosphoric acid are weighed according to the element molar ratio, dispersed in ultrapure water and mixed evenly to form slurry A; then 5% sucrose, 1% PVP, 1% carbon nanotube slurry and 1% graphene slurry are weighed according to the total mass, dispersed in ultrapure water, and added into slurry A to form slurry B; then grind to D50 = 0.25 ± 0.01 microns, and end sand grinding; then spray dry and sinter at 720°C for 10 hours to obtain a carbon-modified high compaction density lithium manganese iron phosphate positive electrode material, namely LMFP material.
[0037] Comparative Example 1: The difference from Example 1 is that only an organic carbon source is used for modification, and the steps are as follows:
[0038] 1379.40g manganese carbonate, 778.97g lithium carbonate, 1207.98g iron phosphate, and 1383.46g concentrated phosphoric acid were weighed, dispersed in 9L ultrapure water and mixed evenly to form slurry A; then 4.8% glucose and 3.2% PEG were weighed according to the total mass, dispersed in 1.5L ultrapure water, and added to slurry A to form slurry B; then ground to D50 = 0.25 ± 0.01 microns, and sand milling was terminated; then spray dried and sintered at 720°C for 10 hours to obtain LMFP material.
[0039] Comparative Example 2: The difference from Example 1 is that only an inorganic carbon source is used for modification, and the steps are as follows:
[0040] 1379.40g manganese carbonate, 778.97g lithium carbonate, 1207.98g iron phosphate, and 1383.46g concentrated phosphoric acid were weighed, dispersed in 9L ultrapure water and mixed evenly to form slurry A; then 10% of the carbon nanotube slurry was weighed according to the total mass, dispersed in 1.5L ultrapure water, and added to slurry A to form slurry B; then ground to D50 = 0.25 ± 0.01 microns, and sand milling was terminated; then spray dried and sintered at 720°C for 10 hours to obtain LMFP material.
[0041] Comparative Example 3: The difference from Example 1 is that the mass ratio of the organic carbon source to the inorganic carbon source is 15:1, and the steps are as follows:
[0042] 1379.40g manganese carbonate, 778.97g lithium carbonate, 1207.98g iron phosphate, and 1383.46g concentrated phosphoric acid were weighed, dispersed in 9L ultrapure water and mixed evenly to form slurry A; then 4.5% glucose, 3% PEG and 0.5% carbon nanotube slurry were weighed according to the total mass, dispersed in 1.5L ultrapure water, and added to slurry A to form slurry B; then ground to D50 = 0.25 ± 0.01 microns, and sand milling was terminated; then spray dried and sintered at 720°C for 10 hours to obtain LMFP material.
[0043] The materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested and characterized. The results are shown in Table 1.
[0044] As can be seen from Table 1, Examples 1 to 4 all use an organic carbon source and an inorganic carbon source mixed in a certain mass ratio as a composite carbon source, which can effectively improve the compaction density of the LMFP positive electrode material while taking into account the discharge capacity. At the same time, its powder conductivity and specific surface area are also relatively good, indicating that it has good electronic conductivity and processability. Among them, Examples 1 and 2 are respectively mixed with an organic carbon source and a single inorganic carbon source, and relatively good compaction density and discharge capacity are achieved; Example 3 uses a mixture of carbon nanotubes and graphene slurry at the same time, and the maximum compaction density reaches 2.46g / cm 3 , the discharge capacity is further improved; Example 4 replaces the organic carbon source with sucrose and PVP, mixes carbon nanotubes and graphene as two inorganic carbon sources, the 0.1C discharge capacity reaches 156.67mAh / g, and the compaction density reaches 2.4g / cm 3 above.
[0045] Comparative Example 1 uses only an organic carbon source as a carbon precursor, and its compaction density is only 2.12, and the powder conductivity is poor and the specific surface area is large, indicating poor electronic conductivity and processing performance; Comparative Example 2 uses only carbon nanotube slurry as a carbon source. Although it has a small specific surface area, its powder conductivity is poor, the compaction density is low, and the 0.1C discharge specific capacity is also low; Comparative Example 3 uses an organic carbon source and an inorganic carbon source to be mixed in a mass ratio of 15:1. Its powder conductivity is poor, the specific surface area is large, and the compaction density is not high, indicating that the use of too low an inorganic carbon source cannot well improve the material's electronic conductivity, discharge capacity, and processing performance.
[0046] Table 1 Material performance test table of Example 1-Example 4 and Comparative Example 1-Comparative Example 3
[0047]
[0048] The material performance test characterization prepared in Example 4 is shown in Figure 1-Figure 3 . Figure 1 The charge and discharge curve of the sample of Example 4 in the voltage window of 2-4.5V is shown, showing the dual voltage platforms of Mn and Fe, and its discharge specific capacity reaches more than 155mAh / g. Figure 2 The SEM image of the sample of Example 4 is shown, showing that carbon nanotubes are interspersed between the LMFP particles, indicating the successful construction of a three-dimensional conductive network. Figure 3 This indicates that LMFP was successfully prepared in Example 4. Combined with its powder conductivity of 8.954E-02S / cm, it shows that the construction of a three-dimensional conductive network can effectively improve the migration and transmission of electrons and effectively improve the electronic conductivity of the material. At the same time, it also has an excellent discharge specific capacity of 156.67mAh / g, which greatly improves the charge and discharge performance of the LMFP material.
[0049] In Comparative Examples 1 to 3, only using an organic carbon source or using an inorganic carbon source with too low a component as a carbon precursor cannot improve the physical, chemical and electrochemical properties of LMFP. This is mainly due to the inability to achieve carbon coating and the construction of a three-dimensional conductive network, the inability of electrons to migrate and conduct well, and the inability to improve electronic conductivity, charge and discharge performance, and processing performance. Using only an inorganic carbon source as a carbon precursor easily forms more LMFP bare shells, cannot achieve carbon coating well, is not conducive to electron migration and conduction, and has poor performance.
Claims
1. A lithium manganese iron phosphate positive electrode material with high compaction density, characterized in that: A carbon layer formed by a composite of an organic carbon source and an inorganic carbon source is coated on the surface of the lithium manganese iron phosphate positive electrode material, wherein the mass ratio of the organic carbon source to the inorganic carbon source is 1.5-5:
1.
2. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The organic carbon source is one or more of glucose, sucrose, fructose, polyvinyl alcohol, polyethylene glycol, polystyrene, polyethylene, polypropylene, starch, cellulose, cyclodextrin, citric acid, ascorbic acid, tartaric acid, palmitic acid, oleic acid, maleic acid, malonic acid, adipic acid, stearic acid, and polyvinyl pyrrolidone.
3. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The inorganic carbon source is one or more of acetylene black, carbon fiber, carbon nanotube, graphene, graphene oxide and modified materials thereof.
4. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The sand-grinding particle size D50 of the lithium manganese iron phosphate positive electrode material is 0.12-0.45 μm.
5. A method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The following steps are involved: (1) dispersing a manganese source, an iron source, a phosphorus source and a lithium source in a solvent and mixing them to obtain slurry A; (2) dispersing a mixed carbon source including an organic carbon source and an inorganic carbon source in a solvent, mixing the mixed carbon source and adding the mixed carbon source to slurry A to obtain slurry B; (3) Slurry B is fully ground, spray-dried, and sintered to obtain a lithium manganese iron phosphate positive electrode material with a high compaction density.
6. The preparation method according to claim 5, characterized in that: In step (1), the molar ratio of the manganese source, iron source, phosphorus source and lithium source is x:1-x:1:1, and x is 0.5-0.
8.
7. The preparation method according to claim 5, characterized in that: In step (1), the molar concentration of the manganese source in the slurry A is 0.5-2.0 mol / L.
8. The preparation method according to claim 5, characterized in that: In step (1), the solid content of the slurry A is 15-45%.
9. The preparation method according to claim 5, characterized in that: In step (2), the mixed carbon source is 5-10% of the total mass of the manganese source, iron source, phosphorus source and lithium source.
10. The preparation method according to claim 5, characterized in that: In step (3), the particle size D50 of the ground material is 0.12-0.45 μm; the spray drying parameters are: air inlet temperature is 220-300°C, and air outlet temperature is 80-100°C; the sintering conditions are: sintering at 650-750°C for 2-10h.